Ghost Squad - Ortega, Claribel A. (New York : Scholastic Press, 2020)
Shortly before Halloween, Lucely and her best friend, Syd, cast a spell that accidentally awakens malicious spirits, wreaking havoc throughout St. Augustine. Together, they must join forces with Syd's witch grandmother, Babette, and her tubby tabby Chunk, to fight the haunting head-on and reverse the curse to save the town and Lucely's firefly spirits before it's too late.
Pub Weekly, March 2020
Booklist, February 2020
Kirkus Review, January 2020
3-6
810L
OBOB MS 2022-2023
Keywords: Best friends -- Juvenile fiction; Witches -- Juvenile fiction; Supernatural -- Juvenile fiction; Best friends -- Fiction; Witches -- Fiction; Ghosts -- Fiction; Supernatural -- Fiction; Ghost stories; Paranormal fiction; Fantasy fiction